Prevalence of Hepatitis B in admitted students of a Private Medical College - Khan, M Karim; Ahmed, KH Golam Sabbir; Ansari, Nazma Parvin; Jahan, Mst Khurshida (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13856 Community Based Medical Journal Vol.1(2) 2012 3-7